1989
DOI: 10.1017/s0003356100003895
|View full text |Cite
|
Sign up to set email alerts
|

Digestibilities of nitrogen and amino acids in soya-bean, sunflower, meat and rapeseed meals measured with pigs and poultry

Abstract: In order to determine the relative digestibilities of nitrogen and amino acids in foodstuffs for pigs and poultry, and the effects of manufacturing methods, equal quantities of soya-bean meal, sunflower meals [hulled (sunflower meal 1) and dehulled (sunflower meal 2)], meat meals [made with (meat meal 1), and without (meat meal 2), blood added at 250 g/kg meat tissue (wet weights)] and rapeseed meals [seeds heated at 80°C (rapeseed meal 1) or 100°C (rapeseed meal 2)] were mixed with protein-free ingredients. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
30
1
2

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 51 publications
8
30
1
2
Order By: Relevance
“…Lower TD values for RSM than for SBM were in agreement with the results of many authors (Sauer et al 1982;Green and Kiener 1989;de Lange et al 1990;Lechevestrier 1996;National Research Council 1998). However, the extent of the difference between the two types of oilseed meal was, in some instances, lower than in the current study (Sauer et al 1982;Green and Kiener 1989).…”
Section: True Digestibility Values and Estimates Of Endogenous Aa Lossessupporting
confidence: 91%
See 1 more Smart Citation
“…Lower TD values for RSM than for SBM were in agreement with the results of many authors (Sauer et al 1982;Green and Kiener 1989;de Lange et al 1990;Lechevestrier 1996;National Research Council 1998). However, the extent of the difference between the two types of oilseed meal was, in some instances, lower than in the current study (Sauer et al 1982;Green and Kiener 1989).…”
Section: True Digestibility Values and Estimates Of Endogenous Aa Lossessupporting
confidence: 91%
“…However, the extent of the difference between the two types of oilseed meal was, in some instances, lower than in the current study (Sauer et al 1982;Green and Kiener 1989). Green and Kiener (1989) and Mariscal-Landin (1992) reported differences in TD values between RSM and SFM of similar magnitude to those in the current study. In agreement with the current results, Knabe et al (1989) and Hennig et al (1993) found N and AA in SFM overall less digestible than in SBM.…”
Section: True Digestibility Values and Estimates Of Endogenous Aa Lossescontrasting
confidence: 63%
“…Thus it is probable that the higher availability estimates reported by Leibholz (1 986) were due to problems in methodology and the use of inappropriate criteria of response. Green & Kiener (1989) reported similar values for true digestibilities and availabilities of lysine in soya-bean (0.84, 0.82) and sunflower (0.84, 082) meals but concluded that as a result of the large standard errors associated with the availability estimates (0.12 and 0.1 8 for soyabean and sunflower meals respectively) no meaningful comparisons could be made.…”
Section: Relationship Between Ileal Digestibility a N D Availabilitymentioning
confidence: 97%
“…found no effect of cecectomy on AA digestibility in grains but observed little variation for oilseed meals. Green and Kiener (1989) documented similar true AA digestibility of soybean meal and sunflower meal in intact and cecectomized roosters. However, considerable decline in AA digestibility of the meat and bone meal and the feather meal was observed in cecectomized birds than intact birds (Green and Kiener, 1989;Parsons, et al, 1997).…”
Section: Amino Acid Digestibility Techniquesmentioning
confidence: 63%
“…Green and Kiener (1989) documented similar true AA digestibility of soybean meal and sunflower meal in intact and cecectomized roosters. However, considerable decline in AA digestibility of the meat and bone meal and the feather meal was observed in cecectomized birds than intact birds (Green and Kiener, 1989;Parsons, et al, 1997). In recent years, with increasing animal welfare concerns, approval of surgical procedures for cecectomy is becoming difficult by Institutional Animal Care and Use Committees.…”
Section: Amino Acid Digestibility Techniquesmentioning
confidence: 63%